The Portuguese law on social economy - Meira, Deolinda Maria Moreira Aparício (2013)
This study is a reflection on the Portuguese Framework Law on Social Economy, highlighting, from a critical point-of-view, its contribution to the explicit institutional and legal recognition of the social economy sector. It does so by defining the concept of social economy and listing the entities engaged in this sector, by defining its guiding principles and the mechanisms for its promotion and encouragement, and also by describing the creation of a tax and competition regime which will take into account its specificities. The setting up of this foundations of the social economy was based on the constitutional principle of protection of the social and cooperative sector, which substantiates the adoption of differentiating solutions in view of the positive discrimination of this sector.